2021
DOI: 10.1371/journal.pone.0254948
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia nervosa and disordered eating attitudes among Lebanese adults: Assessing psychometric proprieties of the ORTO-R in a population-based sample

Abstract: Background Previous research demonstrated a relationship between ON and disordered eating symptoms (eating concern, restraint, cognitive preoccupations about body shape and weight) and disordered eating attitudes (DEA). Since screening for orthorexia nervosa is now part of clinical practice, the measurement instruments to be used must be clinically significant, reliable, valid and sensitive to our target population. The main objective of the present study was to confirm the factor structure of the Arabic versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…Our data support the reliability of the ORTO-R as a measure for ON symptoms, reporting for the instrument a good internal consistency as measured by Cronbach's alpha coefficient. The value of 0.740 reported in our sample is in line with those reported for the ORTO-R in other languages ( 46 48 ) and with the measures of reliability reported in the original validation study ( 19 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data support the reliability of the ORTO-R as a measure for ON symptoms, reporting for the instrument a good internal consistency as measured by Cronbach's alpha coefficient. The value of 0.740 reported in our sample is in line with those reported for the ORTO-R in other languages ( 46 48 ) and with the measures of reliability reported in the original validation study ( 19 ).…”
Section: Discussionsupporting
confidence: 91%
“…As in the case of the ORTO-15, the ORTO-R has been developed in Italian and English, while its Italian version has been used for the validation study, performed in an Italian population ( 18 , 19 ). The questionnaire has also been validated in Arabic ( 46 , 47 ) and Greek ( 48 ), confirming good psychometric properties. A Turkish version has been developed on the basis of the Turkish ORTO-11 ( 49 ).…”
Section: Methodsmentioning
confidence: 77%
“…Although the content of items in ORTO-R was modified [ 23 ], the factor validity of this modified measure has never been actually assessed. Furthermore, existing studies, including the one conducted in the Lebanese population, used items in their original, unmodified meaning [ 27 ]; thus, they are re-assessment of the best working items of the ORTO-15 rather than an adaptation and validation of the ORTO-R items. Second, we aim to assess its validity in regards to disordered eating attitudes, perfectionism, and other relevant variables such as self-esteem, depression, anxiety, and body dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, only a small correlation with the ORTO was observed [ 55 , 56 ]. While we used the items included in a revised version of this scale, we used the original wording of the items and not the revised, which might have influenced the obtained results [ 48 , 49 ]. Summing up, results obtained in the current study supports the validity of the DOS.…”
Section: Discussionmentioning
confidence: 99%
“…The ORTO questionnaire [ 16 ], which has been previously validated in Lebanon [ 47 ], is composed of 15 items, to which respondents answer using a four-point Likert scale 4-point Likert-scale ranging from 1 = always and 4 = never. Within the current study, we used the six items of the original scale (ORTO-R scale), which demonstrated best psychometric qualities [ 18 , 19 ] and is validated in Lebanon [ 48 ]. In this study, the internal consistency of the measure was acceptable (α = 0.72).…”
Section: Methodsmentioning
confidence: 99%